Strategen im Literaturkampf: Thomas Bernhard, Peter Handke und die Kritik - Gschwandtner, Harald (2021)
"Strategen im Literaturkampf" is dedicated to the complex relationship between literary writing, poetological reflection and critical commentary using the example of the Austrian writers Thomas Bernhard and Peter Handke. Harald Gschwandtner shows how closely the two authors' aversion to literary criticism is linked to the principles of their own writing. Prose texts, plays, reviews, interviews, speeches, letters and numerous other work materials allow a variety of insights into a conflict-ridden relationship.